Charlie Joe Jackson's guide to Planet Girl - Greenwald, Tom, 1962- (Greenwald, Tom, 1962- Charlie Joe Jackson book., 2015)
"Everyone has a girlfriend except Charlie Joe! But he won't be left in the dust. Look out for make-ups, break-ups, and hilarious romance tips as Charlie Joe figures out this crazy little thing called love"--